Making of a Good Teacher: Transformative Expressions of Inner Life in Education Narratives of Living, Being and Knowing Together - Ojha, Gaurav (Journal of Education and Research, 2017)
This research paper recollects transformative expressions of inner life in education using expressive language to reconstruct experiential narratives of educators following on with collaborative turn as encouraged in qualitative research. Similarly, this paper reflects on transformative expressions of inner life in education by putting together first person monologues of educators, generated through dialogues. This paper, in addition, reveals their lived pedagogical experiences, their stories, hopes, courage, convictions, creativity and struggles in an education system where educators are most often encouraged to suppress their inner self, somewhere clandestine rather than share the relational richness of their inner life with students. Besides, the paper argues that good teaching takes its reference from inner landscape of an educator. My research participants are aware that by making a difference in their inner life and by infusing transformative orientations of their inner life within their educational practices, they can also make a difference in the lives of their students. They are able to sustain transformative interpersonal relationships with their students, which encourage them to live a life of self-awareness, freedom, character, joy, appreciation, acceptance and creativity. Finally, the paper ends with a realisation that inner life of an educator, including his/her compassion, courage, concern and care, serves as a guiding force for a meaningful relationship that creates transformative possibilities in education.